Hubungan Peran Jender dan Tingkah Laku Pengambilan Risiko pada Wirausaha Perempuan dengan Usaha Kecil - Rachel Arinii; Wustari Mangundjaja; Gagan Hartana TB (Fakultas Psikologi Universitas Pancasila, 2010)
The purpose of this study was to examine the correlation between gender and risk-taking behavior among small-scale female entrepreneurs in Jakarta, Bogor, Depok, Tangerang, dan Bekasi. Female entrepreneur play important role in small scale business. In Indonesia, 99.8% of business are small-scale and 75.6% of small-scale business. player are woman (Mangunsong-Siahaan, 2006). This was a quantitative study with correlational method. The result showed that most small-scale female entrepreneurs played androgynous role and demonstrated moderate risk-taking behavior in high level. Also, there was positive and significant correlation between gender and risk-taking behavior. Feminine gender role associated 48% to risk-taking behavior.